Crotalus durissus terrificus crotapotin naturally displays preferred positions for amino acid substitutions - de Oliveira, Laudicéia Alves [UNESP]; Ferreira, Rui Seabra [UNESP]; Barraviera, Benedito [UNESP]; de Carvalho, Francilene Capel Tavares [UNESP]; de Barros, Luciana Curtolo [UNESP]; dos Santos, Lucilene Delazari [UNESP]; Pimenta, Daniel Carvalho [UNESP] (Springer Nature, 2017)
Background: Classically, Crotalus durissus terrificus (Cdt) venom can be described, according to chromatographic criteria, as a simple venom, composed of four major toxins, namely: gyroxin, crotamine, crotoxin and convulxin. Crotoxin is a non-covalent heterodimeric neurotoxin constituted of two subunits: an active phospholipase A2 and a chaperone protein, termed crotapotin. This molecule is composed of three peptide chains connected by seven disulfide bridges. Naturally occurring variants/isoforms of either crotoxin or crotapotin itself have already been reported. Methods: The crude Cdt venom was separated by using RP-HPLC and the toxins were identified by mass spectrometry (MS). Crotapotin was purified, reduced and alkylated in order to separate the peptide chains that were further analyzed by mass spectrometry and de novo peptide sequencing. Results: The RP-HPLC profile of the isolated crotapotin chains already indicated that the α chain would present isoforms, which was corroborated by the MS and tandem mass spectrometry analyses. Conclusion: It was possible to observe that the Cdt crotapotin displays a preferred amino acid substitution pattern present in the α chain, at positions 31 and 40. Moreover, substitutions could also be observed in β and γ chains (one for each). The combinations of these four different peptides, with the already described chains, would produce ten different crotapotins, which is compatible to our previous observations for the Cdt venom.
Keywords: Crotalus durissus terrificus; Crotapotin; Crotoxin; Isoforms; Venom